2016
DOI: 10.1111/mpp.12378
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of Pectobacterium carotovorum by loop‐mediated isothermal amplification

Abstract: Potatoes are an important agroeconomic crop worldwide and maceration diseases caused by pectolytic bacterial pathogens result in significant pre- and post-harvest losses. Pectobacterium carotovorum shares a common host range with other Pectobacterium spp. and other members of the Enterobacteriaceae, such as Dickeya spp. As these pathogens cannot be clearly differentiated on the basis of the symptoms they cause, improved methods of identification are critical for the determination of sources of contamination. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…LAMP methods for detection of the closely related genera Pectobacterium and Dickeya have already been developed by Yasuhara-Bell and coworkers 16 , but LAMP assays have the disadvantage of requiring a high temperature for amplification (65 °C) and an expensive instrument. RPA is a comparatively new isothermal technique that can detect target DNA in 15–30 min at 37–42 °C with no requirement for sophisticated and/or expensive instruments 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP methods for detection of the closely related genera Pectobacterium and Dickeya have already been developed by Yasuhara-Bell and coworkers 16 , but LAMP assays have the disadvantage of requiring a high temperature for amplification (65 °C) and an expensive instrument. RPA is a comparatively new isothermal technique that can detect target DNA in 15–30 min at 37–42 °C with no requirement for sophisticated and/or expensive instruments 20 .…”
Section: Discussionmentioning
confidence: 99%
“…These include: strand displacement amplification (SDA) 10 , loop-mediated isothermal amplification (LAMP) 11 , rolling circle amplification (RCA) 12 , helicase-dependent amplification (HDA) 13 , recombinase polymerase amplification (RPA) 14 and nicking enzyme amplification reaction (NEAR) 15 . Yasuhara‐Bell and coworkers 16 (2016) reported the development of a specific loop-mediated isothermal amplification (LAMP) assay to detect the blackleg pathogen, P . atrosepticum and soft rot pathogen, P .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported on the LAMP-based detection of P. carotovorum [28]. However, detection technology regarding P. aroidearum has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…To date, LAMP assays have been applied to the diagnosis of some Pectobacterium species [28]. However, these assays are not capable of specifically detecting P. aroidearum .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, it can be easily performed at the point-of-care. It has been successfully used for rapid and specific detection of plant bacteria from infected plant tissues and soil 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%